Pengaruh Dimensi Kualitas Pelayanan terhadap Kepuasan Nasabah dan Dampaknya pada Loyalitas Nasabah PT Sun Life Financial Indonesia di Jakarta - Suharyono Suharyono; Dini Setyo Azani (Neolectura, 2021)
This study analyzes the quality dimension of customer service at PT Sun Life Financial Indonesia on customer satisfaction and its impact on customer loyalty. This study uses a survey method by disseminating questionnaires to customers in PT Sun Life Financial Indonesia as the respondent. Quantitative research method using technical analysis structural equation modeling (SEM) with application AMOS 22. The study used samples from 155 respondents. The results showed that the quality dimension of services such as responsiveness, assurance, empathy, and reliability has a positive and significant effect on customer satisfaction and has a positive and significant impact on customer loyalty.